The Role of Lapor Sleman Application in Enhancing Information Transparency of Sleman Regency Government - Aidan Rizky Ramadhani Haryanto; Rahmat Rian Hidayat; Nopriadi (Journal of Information Technology and Its Utilization, 2025)
Law No. 14 of 2008 requires government transparency in providing public information access. The Sleman Regency Government implemented this mandate through the Lapor Sleman application, despite mixed user reviews among its 10,000+ downloaders. This research examines how this application enhances public information transparency using a qualitative approach through interviews, observations, and documentation. The study applies the Technology Acceptance Model (TAM) theory with five constructs to analyze compliance with Information Commission Regulation No. 5/2016. Results demonstrate that Lapor Sleman successfully increases information transparency by meeting both TAM indicators and transparency requirements, evolving beyond a simple application into a multi-channel reporting service. The integration into Sleman Digital platform represents an innovative response to implementation challenges. This study contributes to e-government literature by analyzing the relationship between technological acceptance and public information transparency. To maximize Lapor Sleman's potential, the research suggests periodic evaluations, improved inter-agency coordination, expanded public education initiatives, and strategic integration with the national SP4N-LAPOR! platform. These recommendations provide a roadmap for strengthening Lapor Sleman as an inclusive, responsive technology-based public service model that can be adapted by other regional governments seeking to enhance transparency through digital platforms.